ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KETIMPANGAN DISTRIBUSI PENDAPATAN - Cendani, Ringga; susilo (Journal of Development Economic and Social Studies, 2022)
This study aims to find out the causes of inequality in the distribution of district/city income in the Province of D.I Yogyakarta and to find out what factors influence the inequality of income distribution of districts/cities in the Province of D.I Yogyakarta. The method used is quantitative by using the trimming model path analysis. The data sources for this research are the Central Bureau of Statistics (BPS) and the Directorate General of Fiscal Balance (DJPK). The results of this study are that the ratio of taxes, capital expenditures and HDI has an effect on the economic growth of districts/cities in the Province of D.I Yogyakarta. Meanwhile, those that affect the inequality of income distribution in the districts/cities of D.I Yogyakarta Province directly are HDI and economic growth and indirectly, namely the ratio of taxes, capital expenditures and HDI with the intervening variable, namely economic growth. Economic growth is an important mediation in influencing the rate of inequality in income distribution. This research is also in accordance with Todaro's theory and Kuznet's hypothesis. It is hoped that this research can assist the district/city government of the Province of D.I Yogyakarta in adopting policies to reduce inequality in income distribution through policies regarding taxes, capital expenditure, improving human quality, and economic growth.